2023
DOI: 10.1186/s40001-023-01050-5
|View full text |Cite
|
Sign up to set email alerts
|

Early identification and treatment for peripheral arterial disease in patients with ischemic cerebrovascular disease

Abstract: Ischemic cerebrovascular disease (ICVD) is a major cause of mortality and disability worldwide and is often caused by atherosclerosis. As a systemic disease, atherosclerosis usually affects multiple vascular beds, mainly including cerebral, coronary, and peripheral arteries. Therefore, ICVD is easily complicated by lower-extremity peripheral arterial disease (PAD). ICVD patients with PAD have more serious symptoms and a worse prognosis, however, neurologists might neglect the evaluation and management of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
0
1
Order By: Relevance
“…Atherosclerosis is a chronic inflammatory disease of the vascular system and is the leading cause of cerebrovascular diseases. 14 Endothelial dysfunction caused by oxidative lipid deposition is the main cause of early atherosclerosis. Therefore, elucidating the mechanism of endothelial dysfunction induced by oxidative lipid deposition may provide promising intervention targets for the treatment of atherosclerosis Herein, we found that ox-LDL-induced HBMEC damage, ferroptosis, and reduced BMAL1 expression in HBMECs, which were all reversed by ferrostatin-1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is a chronic inflammatory disease of the vascular system and is the leading cause of cerebrovascular diseases. 14 Endothelial dysfunction caused by oxidative lipid deposition is the main cause of early atherosclerosis. Therefore, elucidating the mechanism of endothelial dysfunction induced by oxidative lipid deposition may provide promising intervention targets for the treatment of atherosclerosis Herein, we found that ox-LDL-induced HBMEC damage, ferroptosis, and reduced BMAL1 expression in HBMECs, which were all reversed by ferrostatin-1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura corrente ainda sugere que há áreas significativas de incerteza quanto à eficácia das intervenções destinadas a mitigar o risco de AVC em pacientes com DAP. Este panorama requer uma investigação mais aprofundada e sistematizada para esclarecer essas incertezas (Li;Ma, 2023).…”
Section: Introductionunclassified